The Influence of Instagram Social Media and Product Innovation on Consumer Purchasing Decisions at Double Egg Coffee Medan - Habibah, Nurul; Syahreza, Dina; Utami, Nabila; Simanjuntak, Tesya; Fiolin, Fuji; Geopani, Noprin (Economic: Journal Economic and Business, 2024)
This study aims to determine whether there is an influence of Instagram social media and product innovation on consumer purchasing decisions at double egg coffee Medan. This study uses quantitative methods with sample collection techniques using purposive sampling techniques, with a total sample of 116 people who have visited double egg coffee. The data collection technique in this study was carried out by distributing questionnaires whose measurements were on a Likert scale and statistically processed using multiple linear regression analysis which tested the hypothesis with the F test, T test, and the coefficient of determination, before which the data had been tested using validity tests, reliability tests and classical assumption tests. Data management using the SPSS 26 for windows programme. Partially, Instagram social media and product innovation have a positive and significant effect on consumer purchasing decisions at double egg coffee jln. Selamat ketaren no 49-51 mmtc complex (unimed intersection), medan, indonesia 20223.Based on the results of the study, it shows that the social media variables Instagram and product innovation simultaneously influence purchasing decisions. This can be seen from the results of the hypothesis test carried out with the results of the fcount> ftabel value 163.893> 3.07 and the significance value is 0.000 <0.05. The determination coefficient test shows a value of 0.744, which means that social media instagram and product innovation affect purchasing decisions by 74.4% while the rest is influenced by other variables.